The use of video games as a method of architectural education for design students / Nor Mohamad Safuan Fikri Rosli and Suzana Said - Rosli, Nor Mohamad Safuan Fikri; Said, Suzana (2018)
For many years, architectural education has been instructed in class using presentations. Many students are still struggling and having problems in understanding the design language. Architectural education practitioners are only beginning to adopt the more recent and modern techniques. Many advanced countries are using video games as a method of education to help students study interactively in a more fun environment. This paper aims to study the use of video game as a tool for architectural education to help design students understand the basic architectural design languages interactively. This research report was carried out by doing surveys and experimentation. The findings of this research paper indicated that the video game “Minecraft” can help design students to understand and improve their design understanding. The findings concluded that video game can be a tool to help students in understanding design principles